Procesy społeczno-gospodarcze zachodzące we współczesnej przestrzeni Polski na przykładzie aglomeracji wrocławskiej - Drozdowski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper focuses on the issues of globalization and liberalization. It describes the problems concering regionalizm aspects and economic integration of the world. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 250-256